Surface Modification of Multi-Walled Carbon Nanotubes with Polysaccharides - Francisca Larasati; Yuni Kusumastuti; Aswati Mindaryani; Rochmadi Rochmadi; Murni Handayani (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
Multi-walled carbon nanotubes (MWCNTs) are known as efficient drug carriers. To improve their interaction with other materials, surface modification of MWCNTs is necessary. In this work, MWCNTs were functionalized with acid and polysaccharides (chitosan and gelatin). The functionalization process was done via modification with acid solutions of nitric acid, sulfuric acid, and a mixture of nitric acid-sulfuric acid first, followed by functionalization with chitosan and gelatin. To achieve the optimum condition of MWCNTs functionalization, the reaction time, temperature, and acid ratio were varied. Furthermore, the effect of chitosan and gelatin addition into MWCNTs was studied at various mass ratios. The synthesized materials were characterized by Fourier transform infrared spectrophotometer, Boehm titration, and dispersion test. The Boehm titration results showed that the acid functional groups had been attached successfully to MWCNTs surface. The amount of acid functional groups increased along with reaction time. The highest amount of acidic group obtained from the data was 2.33 mmol/g. It was achieved when MWCNTs reacted with nitric acid for 24 hours. Temperature and acid ratio variations on the MWCNTs functionalization did not provide significant results. From the FTIR data, sharp peaks at 3480 cm-1 and 1040 cm-1 indicates a -CONH bond, which shows that chitosan and gelatin have been successfully grafted onto MWCNTs surface via an amide linkage. Moreover, the dispersion test showed that the functionalized materials were stable for 48 hours.